Effect of Alternate Treatment with Intravitreal Corticosteroid and Anti-VEGF for Macular Edema Secondary to Retinal Vein Occlusion - Young Hwan Bae; Seong Mi Kim; Jin Young Kim; So Hyun Bae; Hakyoung Kim; Dae Joong Ma (Journal of Ophthalmology)
Purpose. To evaluate whether treatment with intravitreal corticosteroid and anti-vascular endothelial growth factor (VEGF) injections alternately can improve treatment outcomes of macular edema (ME) caused by retinal vein occlusion (RVO). Methods. This dual-center retrospective study included 112 eyes with treatment-naïve ME secondary to RVO that were alternately treated with intravitreal corticosteroid and anti-VEGF injections (33 eyes, alternate group) or treated only with intravitreal anti-VEGF injections (79 eyes, anti-VEGF group) on a pro re nata basis. Results. During the 12-month follow-up period, the alternate group achieved a visual acuity gain of 0.39 logMAR, while the anti-VEGF group achieved a gain of 0.21 logMAR (P=0.042). The alternate group demonstrated a reduction in the central macular thickness of 229.9-μm, while the anti-VEGF group achieved a reduction of 220.1 μm (P=0.887). The alternate group required an average of 5.2 injections, while the anti-VEGF received 4.2 injections (P<0.001). In a propensity score-matched cohort to compensate for the differences in the injection numbers between the two groups, the alternate group achieved a better visual acuity gain than the anti-VEGF group at month 12 (0.39 logMAR vs. 0.17 logMAR, P=0.048). Conclusions. In ME secondary to RVO, treatment with intravitreal corticosteroid and anti-VEGF injections alternately resulted in a more favorable visual outcome compared with intravitreal anti-VEGF monotherapy.